2016
DOI: 10.1093/mnras/stw465
|View full text |Cite
|
Sign up to set email alerts
|

Application of the spine-layer jet radiation model to outbursts in the broad-line radio galaxy 3C 120

Abstract: We present a detailed Fermi/LAT data analysis for the broad-line radio galaxy 3C 120. This source has recently entered into a state of increased γ-ray activity which manifested itself in two major flares detected by Fermi/LAT in September 2014 and April 2015 with no significant flux changes reported in other wavelengths. We analyse available data focusing our attention on aforementioned outbursts. We find very fast variability timescale during flares (of the order of hours) together with a significant γ-ray fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
5
14
0
Order By: Relevance
“…The γ-rays from 3C 120 had been already detected by Fermi LAT during first 15 months' scan of the whole sky (Abdo et al 2010a) which was then confirmed by the data accumulated for two years (Kataoka et al 2011). Also a long-term (several months) variability had been found using the five-year Fermi LAT data (Sahakyan et al 2015) with short periods (days and hours) of brightening (Tanaka et al 2015;Janiak et al 2016). Inverse Compton scattering of synchrotron photons seems to be the mechanism responsible for the γ-ray emission from 3C 120 (Tanaka et al 2015;Sahakyan et al 2015) while the flares and the fast γ-ray variability are explained within more complex structured jet scenarios (Janiak et al 2016).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The γ-rays from 3C 120 had been already detected by Fermi LAT during first 15 months' scan of the whole sky (Abdo et al 2010a) which was then confirmed by the data accumulated for two years (Kataoka et al 2011). Also a long-term (several months) variability had been found using the five-year Fermi LAT data (Sahakyan et al 2015) with short periods (days and hours) of brightening (Tanaka et al 2015;Janiak et al 2016). Inverse Compton scattering of synchrotron photons seems to be the mechanism responsible for the γ-ray emission from 3C 120 (Tanaka et al 2015;Sahakyan et al 2015) while the flares and the fast γ-ray variability are explained within more complex structured jet scenarios (Janiak et al 2016).…”
Section: Introductionmentioning
confidence: 72%
“…Also a long-term (several months) variability had been found using the five-year Fermi LAT data (Sahakyan et al 2015) with short periods (days and hours) of brightening (Tanaka et al 2015;Janiak et al 2016). Inverse Compton scattering of synchrotron photons seems to be the mechanism responsible for the γ-ray emission from 3C 120 (Tanaka et al 2015;Sahakyan et al 2015) while the flares and the fast γ-ray variability are explained within more complex structured jet scenarios (Janiak et al 2016). Combining of the data derived at the sub-pc and kilo-parsec regions of the same jet could greatly help to understand the features of powerful extragalactic jets, e.g., shed some light on the evolution and propagation of the jets from the central engine to the outer regions, where the jet is starting to significantly decelerate.…”
Section: Introductionmentioning
confidence: 92%
“…This progressive slowdown in the apparent velocity of components could be explained by a change in the velocity and/or a change in the orientation of the components. A precession model for 3C 120 has been already proposed by [12] as well as by [13]. Interestingly, in [13], the authors interpreted the γ-ray event in September 2014 considering the jet as formed by a fast spine and a slower outer layer, where it is only the spine that changes its direction and occasionally points more toward the observer, as during γ-ray flares.…”
Section: Mjdmentioning
confidence: 96%
“…A precession model for 3C 120 has been already proposed by [12] as well as by [13]. Interestingly, in [13], the authors interpreted the γ-ray event in September 2014 considering the jet as formed by a fast spine and a slower outer layer, where it is only the spine that changes its direction and occasionally points more toward the observer, as during γ-ray flares. By using the observed apparent velocities, and minimizing the required reorientation of the jet, we could estimate the Lorentz factor Γ = 6.3, and a change in viewing angle from 9.2 • to 3.6 • , where the latter corresponds to the epoch of the ejection of component d11 and the γ-ray event.…”
Section: Mjdmentioning
confidence: 96%
“…Even when the emission is most likely produced in a compact region of the jet (e.g., Cen A core (Abdo et al 2010d), M87 (Abdo et al 2009b) and NGC 1275 (Abdo et al 2009a)), the most popular one-zone synchrotron/synchrotron self Compton (SSC) model clearly fails to explain the observed multiwavelength properties. More complicated models, multi-zone (Lenain et al 2008) or structured jet (Tavecchio & Ghisellini 2008;Janiak et al 2016;Tavecchio & Ghisellini 2014), based on different assumptions should be employed to explain the observed data properly. New and high-quality data are still needed to fully understand the origin of multiwavelength emission from non-blazar AGNs.…”
Section: Introductionmentioning
confidence: 99%